A sociocultural perspective surrounding the application of global positioning system technology: Suggestions for the strength and conditioning coach - Jones, L.; Denison, J. (Strength and Conditioning Journal, 2018)
An increased use of global positioning system (gps) monitoring within professional sport has led to an evolution in the role of the strength and conditioning (s&c) coach. This role continues to gravitate toward a greater emphasis on the collection, discernment, and application of gps data. However, there are numerous implications surrounding the use of monitoring technologies by coaches that sport sociologists have shown through the work of french philosopher michel foucault that can be potentially problematic for athletes' development. S&c coaches now require guidance to help them to use these tools. Here, we present some suggestions to help the s&c coach in this endeavor.